Iron-catalysed oxidative cleavage of lignin and β-O-4 lignin model compounds with peroxides in DMSO. Issue 11 (27th August 2015) - Mottweiler, Jakob; Rinesch, Torsten; Besson, Claire; Buendia, Julien; Bolm, Carsten
Abstract : Simple FeCl3 -derived iron catalysts are used for the cleavage of lignin and β-O-4 lignin model compounds. Abstract : Simple FeCl3 -derived iron catalysts are used for the cleavage of β-O-4 linkages in lignin and lignin model compounds. The degradation of the β-O-4 linkages and the resinol structures in both organosolv and kraft lignin was proven by 2D-NMR (HSQC) experiments, and the oxidative depolymerisation of these lignin sources was confirmed by GPC. Key reactive species facilitating this cleavage are methyl radicals generated from H2 O2 and DMSO.